Lived religion, Pentecostalism, and social activism in authoritarian Chile: giving life to the faith - Florez, Joseph (Religion in the Americas series, 2021)
Echoes of the Awakening -- Memory and every day religious experience in Pinochet's Chile -- Pentecostal community activism -- Hacer Vica la Fe -- A prohibited history of Pentecostal social engagement.